Using the project-level Women's Empowerment in Agriculture Index (pro-WEAI) for nutrition sensitive programming - Malapit, Hazel J.; Heckert, Jessica; Martinez, Elena M. (International Food Policy Research Institute, 2018)
Presented by Hazel Malapit, Jessica Heckert and Elena Martinez (A4NH / IFPRI), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.